Textual Strategies : Perspectives in Post-Structuralist Criticism - Harari, Josue V. (Cornell University Press, 2019)
A stellar cast of fifteen contributors seeks to show the direction in which continental and continentally oriented American literary criticism has evolved in recent years. Nine of the essays are published here for the first time; five of the remaining six were translated, by the editor, from the French; only one has previously appeared in English.The essays make available some of the most important and most representative work that has been done in the wake of structuralism. Among the topics treated are the relationships between semiology and literature, anthropology and literature, and psychoanalysis and literature; modern American poetics; algebraic models as epistemological operators; the modes of production of a poem; Flaubert's view of history; and poetic language. Professor Harari has arranged the essays to move from the general to the particular and from the abstract to the concrete. In an informative and ambitious introduction, he discusses each essay in relation to the whole and explains the interrelationships among the various theories and strategies that are represented in the anthology.A book meant for the specialist as well as the novice, for the teacher of literature and criticism as well as the student, Textual Strategies is a brilliant introduction to post-structuralist critical theories and practices.